Distributional Effects of Macroeconomic Shocks in Real-Time: A Novel Method Applied to the Covid-19 Crisis in Germany - Kerstin Bruckmeier; Andreas Peichl; Martin Popp; Jürgen Wiemers; Timo Wollmerhäuser (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
The highly dynamic nature of the COVID-19 crisis poses an unprecedented challenge to policy makers around the world to take appropriate income-stabilizing countermeasures. To properly design such policy measures, it is important to quantify their effects in real-time. However, data on the relevant outcomes at the micro level is usually only available with considerable time lags. In this paper, we propose a novel method to assess the distributional consequences of macroeconomic shocks and policy responses in real-time and provide the first application to Germany in the context of the COVID-19 pandemic. Specifically, our approach combines different economic models estimated on firm- and household-level data: a VAR-model for output expectations, a structural labor demand model, and a tax-benefit microsimulation model. Our findings show that as of September 2020 the COVID-19 shock translates into a noticeable reduction in gross labor income across the entire income distribution. However, the tax benefit system and discretionary policy responses to the crisis act as important income stabilizers, since the effect on the distribution of disposable household incomes turns progressive: the bottom two deciles actually gain income, the middle deciles are hardly affected, and only the upper deciles lose income. – – Die hohe Dynamik der COVID-19-Krise stellt die politischen Entscheidungsträger in aller Welt vor die beispiellose Herausforderung, geeignete Maßnahmen zur Einkommensstabilisierung zu ergreifen.Umsolche Maßnahmen angemessen auszugestalten, ist es wichtig, ihre Auswirkungen in Echtzeit zu quantifizieren. Die hierfür benötigten Daten sind jedoch in der Regel nur mit erheblichen Zeitverzögerungen verfügbar. In diesem Papier entwickeln wir einen neuen Ansatz, um die Verteilungswirkungen von makroökonomischen Schocks und der daraus folgenden Politikmaßnahmen in Echtzeit zu analysieren. Unser Ansatz kombiniert verschiedene ökonomische Modelle, die auf Unternehmens- und Haushaltsdaten geschätztwerden: ein VAR-Modell für die Produktionserwartungen, ein strukturelles Arbeitsnachfragemodell sowie ein Mikrosimulationsmodell. Wir wenden unsere Methode im Kontext der COVID-19-Pandemie auf Deutschland an. Unsere Ergebnisse zeigen, dass die COVID-19-Krise sich in einer spürbaren Verringerung des Bruttoarbeitseinkommens über die gesamte Einkommensverteilung hinweg niederschlägt. Das Steuer-Transfer-System und diskretionäre Krisenmaßnahmenfungieren jedoch als Einkommensstabilisatoren und sorgen dafür, dass der Effekt auf die Verteilung der verfügbaren Haushaltseinkommenprogressiv verläuft. Die unteren beiden Dezilgruppen gewinnen Einkommen, die mittleren Einkommensgruppen sind kaum betroffen und nur die oberen Dezile verlieren Einkommen.
Keywords: D31; E24; E37; H24; J23; 330; income distribution; inequality; recession; COVID-19; tax-benefit policies; short-time work; business survey; labor demand; microsimulation